Immune‐Hot tumor features associated with recurrence in early‐stage ovarian clear cell carcinoma - Huang, Ruby Yun‐Ju; Huang, Kuan‐Ju; Chen, Ko‐Chen; Hsiao, Sheng‐Mou; Tan, Tuan Zea; Wu, Chin‐Jui; Hsu, Ching; Chang, Wen‐Chun; Pan, Chen‐Yu; Sheu, Bor‐Ching; Wei, Lin‐Hung (International journal of cancer, 2023)
Ovarian clear cell carcinoma (OCCC) is a distinct histotype of ovarian cancer, which usually presages a worse prognosis upon recurrence. Identifying patients at risk for relapse is an unmet need to improve outcomes. A retrospective cohort analysis of 195 early‐stage OCCC patients diagnosed between January 2011 and December 2019 at National Taiwan University Hospital was conducted to identify prognostic factors for recurrence, progression‐free survival (PFS) and overall survival (OS). Molecular profiling of tumors was performed in a case‐controlled cohort matched for adjuvant therapy for biomarker discovery. Multivariate Cox proportional hazard model revealed that paclitaxel‐based chemotherapy was associated with better PFS than nonpaclitaxel chemotherapy (HR = 0.19, P = .006). The addition of bevacizumab was associated with better PFS, compared to no bevacizumab (HR = 0.09, P = .02). Neither showed significant improvement in OS. Recurrence is associated with an Immune‐Hot tumor feature (P = .03), the CTLA‐4‐high subtype (P = .01) and increased infiltration of immune cells in general. The Immune‐Hot feature (HR = 3.39, P = .005) and the CTLA‐4‐high subtype (HR = 2.13, P = .059) were associated with worse PFS. Immune‐Hot tumor features could prognosticate recurrence in early‐stage OCCC. What's new? While adjuvant irradiation can improve progression‐free survival (PFS) in ovarian clear cell carcinoma (OCCC), control of metastatic disease remains a challenge. Especially problematic is the lack of optimal treatment for recurrent OCCC. In the present retrospective analysis, the addition of bevacizumab to paclitaxel‐based chemotherapy was associated with improved PFS in early‐stage OCCC patients. Moreover, molecular profiling revealed correlations between OCCC recurrence and immune‐hot tumor feature, CTLA‐4‐high subtype and increased immune cell infiltration. The findings suggest that immune profiling can help identify OCCC patients who are at risk for relapse and who may benefit from combined paclitaxel‐based chemotherapy and bevacizumab therapy.